P67 The relationship between socio-economic class and work-related mental ill-health. (2nd September 2017) - Hussey, L; Money, A; Gittins, M; Agius, R
Abstract : Background: Inequalities in health are often described showing an inverse relationship with social economic group and mortality and morbidity. However, work-related mental ill-health (WRMIH) reported by GPs show highest rates amongst higher socio-economic groups, particularly 'Lower managerial and professional' and 'Intermediate' occupations. Similar results are shown with the self-reported WRMIH collected by the Self-reported Work-related Illness (SWI) survey as part of the Labour Force Survey (LFS). The Health and Occupation Research network (THOR) collects data on WRMIH from GPs, occupational physicians (OPs) and psychiatrists. This study aimed to analyse the psychosocial factors associated with the WRMIH reported in different socio-economic groups. Methods: With each case of WRMIH, participating physicians report information including occupation and the psychological stressor considered to be associated with the condition. Occupational data were coded using the National Statistics Socio-Economic Classification (NS-SEC). A multi-level logistic regression calculated odds ratios (ORs) (adjusted by age and gender) reporting the likelihood of the stressor occurring within each socio-economic group compared to the highest reference group 'Large employers and higher managerial occupations'. Results: Results showed that the socio-economic groups were exposed to significantly different workplace stressors. Cases reported from the highest group were more likely to be associated with workload and workplace change with ORs falling as socio-economic status decreased, e.g. for workload, ORs in the lowest NS-SEC group were 0.51 (GPs), 0.14 (OPs) and 0.16 (psychiatrists). Lower NS-SEC groups were more likely to have problems associated with bullying and interpersonal relationships, e.g. for bullying, ORs in the lowest group were 2.60 (GPs), 1.76 (OPs) and 1.60 (psychiatrists). Conclusion: WRMIH rates may be greatest amongst higher socio-economic groups as they are more likely to have problems associated with a heavy workload and changes in the workplace such as staff shortages and organisational restructure. NS-SEC groups with highest rates such as the 'middling' lower managerial and intermediate occupations may find themselves caught in the middle and experience the "worst of both worlds", i.e. they feel responsibility for the success of the workplace, have demands from those in higher managerial positions, but also have to deal with issues surrounding the maintenance of interpersonal relationships with other workers, clients, patients or pupils. Information from this study may help develop workplace interventions targeted to prevent psychosocial factors affecting different sections of the workforce.